Proletarii vsekh stran, soyedinyaites'
Red army soldier attacking tank-shaped robot with the appearance of capitalist Original title: Пролетарии всех стран, соединяитесь Suggested translation: Proletarians of all countries, unite; Item is framed; dimensions: 1110 X 800 mm PO-2504